Analisis Pengaruh Dana Pihak Ketiga dan Modal Terhadap Likuiditas Bank Umum Syariah di Indonesia Periode 2017-2019 - Minarni, Desi (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2021)
The main purpose of establishing Islamic financial institutions is to prosper the people and earn profits. Financing is one of the main components of Islamic Banks in generating profits. The development of Islamic Banking financing in Indonesia has increased as many parties invest their funds in Islamic Banks. Customers and investors are the biggest contributors of funds to the bank. For this reason, banks must have a good strategy to attract customers to invest their funds in Islamic Banks. Therefore, this study aims to examine the factors of third party funds and capital on financing by measuring how much influence they have on the financing. This type of research is included in descriptive quantitative research using secondary data sources taken from the official website of the Financial Services Authority. The sample selection used is a saturated sample by making the entire population as a sample. The author uses data collection methods with literature and documentation studies as well as data analysis techniques using descriptive statistics, classical assumption tests and hypothesis testing. The results of this study indicate that Third Party Funds partially have a significant effect on the liquidity of Islamic Commercial Banks in Indonesia for the 2017-2019 period with a probability value of 0.00000 < 0.05. While capital partially does not affect the liquidity of Islamic Commercial Banks in Indonesia for the 2017-2019 period with a value of 0.8067 > 0.05. However, Third Party Funds and capital simultaneously have a significant effect on the liquidity of Islamic Commercial Banks in Indonesia for the 2017-2019 period with a probability value of 0.000000 < 0.05 significance value.